The bear and the nightingale : a novel - Arden, Katherine (New York : Del Rey, 2017)
"A magical debut novel for readers of Naomi Novik's Uprooted, Erin Morgenstern'sThe Night Circus, and Neil Gaiman's myth-rich fantasies, The Bear and the Nightingale spins an irresistible spell as it announces the arrival of a singular talent with a gorgeous voice. At the edge of the Russian wilderness, winter lasts most of the year and the snowdrifts grow taller than houses. But Vasilisa doesn't mind--she spends the winter nights huddled around the embers of a fire with her beloved siblings, listening to her nurse's fairy tales. Above all, she loves the chilling story of Frost, the blue-eyed winter demon, who appears in the frigid night to claim unwary souls. Wise Russians fear him, her nurse says, and honor the spirits of house and yard and forest that protect their homes from evil. After Vasilisa's mother dies, her father goes to Moscow and brings home a new wife. Fiercely devout, city-bred, Vasilisa's new stepmother forbids her family from honoring the household spirits. The family acquiesces, but Vasilisa is frightened, sensing that more hinges upon their rituals than anyone knows. And indeed, crops begin to fail, evil creatures of the forest creep nearer, and misfortune stalks the village. All the while, Vasilisa's stepmother grows ever harsher in her determination to groom her rebellious stepdaughter for marriage or confinement in a convent. As danger circles nearer, Vasilisa must defy even the people she loves and call on dangerous gifts she has long concealed--this, in order to protect her family from a threat that seems to have stepped from her nurse's most frightening tales. Advance praise for The Bear and the Nightingale "An extraordinary retelling of a very old tale. A Russian setting adds unfamiliar spice to the story of a young woman who does not rebel against the limits of her role in her culture so much as transcend them. The Bear and the Nightingale is a wonderfully layered novel of family and the harsh wonders of deep winter magic."--Robin Hobb, bestselling author of the Fitz and the Fool trilogy "A beautiful deep-winter story, full of magic and monsters and the sharp edges of growing up."--Naomi Novik, bestselling author of Uprooted"--
"In a village at the edge of the wilderness of northern Russia, where the winds blow cold and the snow falls many months of the year, a stranger with piercing blue eyes presents a new father with a gift - a precious jewel on a delicate chain, intended for his young daughter. Uncertain of its meaning, Pytor hides the gift away and Vasya grows up a wild, willful girl, to the chagrin of her family. But when mysterious forces threaten the happiness of their village, Vasya discovers that, armed only with the necklace, she may be the only one who can keep the darkness at bay"--
Keywords: Young women -- Fiction; Villages -- Fiction; Good and evil -- Fiction; Spirits -- Fiction; Magic -- Fiction; FICTION / Fantasy / General; FICTION / Literary; Russia -- Fiction; Fantasy fiction